1995
DOI: 10.1017/s0033291700033419
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging volumetric measurements of the superior temporal gyrus, hippocampus, parahippocampal gyrus, frontal and temporal lobes in late paraphrenia

Abstract: SYNOPSISQuantified magnetic resonance measurements were made of superior temporal gyrus, parahippocampal gyrus, hippocampal, frontal and temporal lobe volumes and of the planar area of the thalamus and basal ganglia structures in 47 late paraphrenic patients and 33 healthy elderly controls. The late paraphrenics were divided into 31 schizophrenics and 16 patients with delusional disorder according to ICD-10 guidelines. Patients with delusional disorder tended to have smaller left temporal volumes compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 44 publications
2
17
1
1
Order By: Relevance
“…However, the normal human brain has some asymmetry. Right 1 left (R 1 L) asymmetry has been reported in normal subjects when whole hemisphere [14] , temporal [15,16] or frontal lobes [17,18] are compared. Several MRI studies have shown the right hippocampus to be larger than the left in normal subjects [11,15,[19][20][21][22][23][24][25] , with estimates of the magnitude of this asymmetry of up to 10% [19] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the normal human brain has some asymmetry. Right 1 left (R 1 L) asymmetry has been reported in normal subjects when whole hemisphere [14] , temporal [15,16] or frontal lobes [17,18] are compared. Several MRI studies have shown the right hippocampus to be larger than the left in normal subjects [11,15,[19][20][21][22][23][24][25] , with estimates of the magnitude of this asymmetry of up to 10% [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical studies have reported reduced volume (Bogerts, 1993;Bogerts et al, 1993;Gigg et al, 1994;Howard et al, 1995;Shenton et al, 1992), reduction of neuronal size (Arnold et al, 1995), decreases in the number of synaptic connections (Selemon et al, 1995), and disruption of cellular organization (Akbarian et al, 1993;Altshuler et al, 1987) in the hippocampi of schizophrenia patients, with less severe changes in organization also reported in the PFC (Akbarian et al, 1993). These cortical alterations are believed to reflect disruptions occurring during brain development (Akbarian et al, 1993;Bogerts, 1993;Bogerts et al, 1993;Weinberger and Lipska, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…64 Other MRI studies examining the temporal lobe in patients with late-onset psychosis have been inconsistent, reporting smaller volumes [65][66][67] and no differences 68,69 compared to age-matched healthy controls. No difference compared to age-matched controls in late-onset psychosis was reported for the frontal lobe [67][68][69] and the size of the caudate and lenticular nuclei or the thalamus. 68,69 Most studies comparing late-onset psychosis with agematched early-onset psychosis found no significant differences.…”
Section: Neuroimagingmentioning
confidence: 99%
“…No difference compared to age-matched controls in late-onset psychosis was reported for the frontal lobe [67][68][69] and the size of the caudate and lenticular nuclei or the thalamus. 68,69 Most studies comparing late-onset psychosis with agematched early-onset psychosis found no significant differences. As well, no differences between these groups were reported in the size of the lateral and third ventricles, 67 with no reported differences in cortical atrophy.…”
Section: Neuroimagingmentioning
confidence: 99%